Pengaruh Supervisi Akademik Kepala Sekolah Terhadap Kinerja Guru SMA Negeri Di Kota Mataram - Yayuk, Yayuk; Ramdani, Agus; Syafruddin, Syafruddin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
Academic supervision is all efforts made on an ongoing basis to assist teachers and school principals in developing teacher abilities and performance in managing learning. This study aims to determine the effect of principal academic supervision on teacher performance. The research was conducted in all public high schools in the city of Mataram. This research uses a quantitative approach with an ex post facto design. The study population was all permanent teachers in SMA Negeri in Mataram City. The research sample was taken using proportionate random sampling technique. Data collection techniques with questionnaires and simple linear correlation to test the hypothesis of the strength of the relationship between two independent variables together with one dependent variable. The results showed that the principal's academic supervision had an effect on teacher performance (P <0.03). The success of academic supervision carried out by the principal has an important effect on the performance of teachers in SMA Negeri in Mataram City.